Advanced Intelligent Systems for Sustainable Development (AI2SD'2018) Vol 1: Advanced Intelligent Systems Applied to Agriculture - Ezziyyani, Mostafa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book gathers papers presented at the International Conference on Advanced Intelligent Systems for Sustainable Development (AI2SD-2018), which was held in Tangiers, Morocco on 12-14 July 2018. Highlighting the latest research and findings in the field of agriculture, it provides new solutions, efficient tools and techniques that draw on modern technologies to increase agricultural productivity. In addition, it provides a critical overview of the status quo, shares new propositions, and outlines future perspectives in agriculture.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence